Changes in activity of some indicators of pro-oxidant and antioxidant systems in guinea pigs’ lungs in experimental allergic alveolitis and their correction with thiotriazolin - Baida, Mariana Ljubomurivna; Sadljak, Oksana Volodumurivna; Reheda, Stepan Mykhailovuch (Journal of Education, Health and Sport, 2017)
These changes correlate with the development of oxidative stress in animals over the entire duration of the experiment, which manifested by an increase in the content of the lipoperoxidation products (LPO) - conjugated diene level and malonic dialdehide) in the lungs in comparison with control group. Decreasing of the antioxidant activity (a significant reduction of peroxidase and ceruloplazmin level) in the lung`s tissure of guinea pigs has been reported. Correction of these shifts with the antioxidant drug thiotriazolin inhibits accumulation of LPO products and increases antioxidant defense. The experimental data most probably indicate a pronounced effect of thiotriazolin on the realization of the antiinflammatory and antioxidant effects and allows a suggestion about the antiradical mechanism of this drugs.